Semiautomatic Evaluation of Tricuspid Annular Plane Systolic Excursion from Two Dimensional Echocardiographic Images. Issue 5 (11th January 2016) - Ramamurthy, Senthil; Kelleman, Michael S.; McGaughy, Falon; Sachdeva, Ritu
Abstract : Background: Tricuspid annular plane systolic excursion (TAPSE) has emerged as a reliable marker of right ventricular (RV) systolic function. Recently, TAPSE derived using 2D images (2D‐TAPSE) was shown to correlate with M‐mode TAPSE (MM‐TAPSE). We have developed a novel technique for semiautomatic evaluation of TAPSE (SA‐TAPSE). The purpose of this study was to determine the accuracy of this novel technique and validate it on normal hearts and pulmonary hypertension (PH). Methods: A total of 110 patients (56 with normal heart and 54 with PH) were retrospectively identified for analysis. The semiautomatic algorithm tracked the lateral tricuspid valve hinge point (TVHP) and the apex in the apical 4‐chamber view. SA‐TAPSE was calculated as displacement of the TVHP in end‐diastole (ED) and end‐systole (ES). The same points were manually identified to derive 2D‐TAPSE. Results: The system was able to accurately identify ED and ES in 304/330 heartbeats within three cardiac frames. The automatically identified TVHP points were within 1.2 ± 0.7 mm from the manually identified points. Intra‐class correlation between SA‐TAPSE and 2D‐TAPSE was 0.96 (95% CI 0.93–0.98) for normal hearts and 0.92 (95% CI 0.87–0.96) for those with PH. Bland–Altman analysis showed a strong agreement between SA‐TAPSE and 2D‐TAPSE for normal hearts and those with PH. Conclusion: Using the novel custom‐made software, SA‐TAPSE could be measured in majority of our patients and was accurate when applied to normal hearts and those with PH. Future work will focus on fully automating the system for a rapid retrospective analysis of TAPSE.